(untitled) (Annals of Medical Research, 2022)
Aim: Combined pulmonary fibrosis and emphysema (CPFE) and idiopathic pulmonary fibrosis (IPF) have been discussed intensively in recent years as two different entities. We aimed to compare the clinical, functional and respiratory parameters, clinical course and mortality rates of patients with CPFE with IPF. Materials and Methods: 36 patients with a diagnosis of CPFE and 40 IPF who applied between September 2013 and February 2019 were retrospectively included in the study. Demographic data, comorbidities, pulmonary function parameters, life surveys, systolic pulmonary artery pressures(sPAP) detected. Results: In the CPFE patient group, While the ratio of male patients (p=0.02), smoking (p<0.001), number of inflammation (p=0.001) were found to be significantly higher, SF-36 total score (p<0.001) were significantly lower (p=0.02) than the IPF group. While FVC% (p<0.002), FEV1% (p=0.049) and TLC% (p=0.002) were significantly higher in the CPFE group than in the IPF group, TLCO% (p<0.002) and FEV1/FVC (p<0.001) was lower. Pulmonary hypertension (PH) was 40% in CPFE and 37% in IPF and no significant difference was found between them (p=0.806). Those who received long-term oxygen therapy(LTOT) were more common in the CPFE group (p=0.04). In CPFE patients; the percentage of those who received bronchodilator, antifibrotic, systemic corticosteroid was respectively 52.7%, 36.1%, 5.6%. Mortality from any cause was 9(25%) in CPFE and 8(20%) in IPF, and there was no significant difference between the two groups(p=0.601). Conclusion: It was observed that lung volumes were preserved and gas exchange of the lung was significantly decreased in patients with CPFE. Compared to IPF, although the quality of life was lower and inflammation was more common in CPFE, the frequency of PH and mortality were similar in both groups. Male gender and smoking history are important risk factors for this group of patients. There is a need for multicenter studies reporting the clinical features, prognosis, and mortality of CPFE.